RTB Meeting Report: Piloting the G+ Tools - CGIAR Gender and Breeding Initiative (2020)
Over the last three years, the CGIAR Gender and Breeding Initiative (GBI) has been developing the G+ Customer Profile Tool and the G+ Product Profile Query Tool (the G+ Tools) to help integrate gender issues into breeding programs to increase crop varietal adoption and bring about greater social impact. In 2019, the CGIAR Excellence in Breeding Platform (EiB) approved a grant to pilot the G+ Tools in two African-based breeding programs for beans and cassava. The piloting implied integration of the Tools into the EIB product profile development framework. Later CIP, with the support of RTB, incorporated the sweetpotato breeding program in Uganda to be part of the piloting process. Eventually, representatives from the banana and cereals and lentils breeding programs in Uganda and the CWANA region, respectively, also joined the process. A workshop in Nairobi in March 2020 marked the beginning of the piloting project. Following the workshop, each of the piloting teams returned to their home institutions to pilot the Tools and their standard operating procedure (SOP). However, due to the COVID-19 pandemic, changes were made to the original project timeline. Most notably, the project got a no-cost extension until the end of December 2020 and the planned “Evaluation and Learning” workshop was replaced by eight digital meetings taking place from September to December 2020. By generating feedback on the G+ Tools and their SOP, the piloting project was pivotal in advancing towards an alpha version of the Tools, to be released in 2021. Additionally, the piloting helped identify critical gaps in the EiB framework. Through two main rounds of adjustments, the GBI made important suggestions for improving the social inclusiveness and gender responsiveness of the EiB product profile development process, most notably by emphasizing the human face of breeding: the definition of market segments and product profiles should strongly focus on the people – gender and social inclusion should be at the heart of breeding. Thus, addressing in particular those who have been missed by breeding programs or are not currently served by available varieties. The piloting teams further found that the G+ Tools helped facilitate insightful and constructive discussions with breeders and economists on the importance of being gender responsive, including the potential for harmful and beneficial effects of traits on men and women, and how being socially inclusive can lead to increased variety turnover rates. Furthermore, the piloting process has been important in highlighting the need to give voice and power to gender researchers in developing, monitoring, and evaluating market segmentation and product profiles. Many participants felt that the piloting project was only the beginning – a first, essential step towards the goal of rendering breeding programs gender responsive. For most, the G+ Tools helped identify key information gaps that should be communicated to higher management levels, donors, and other partners: the data gaps suggest the need to reallocate effort and budgets towards understanding, ex ante, what the customer landscape looks like.